STRATEGY OF THE MINISTRY OF ECONOMIC COORDINATOR IN THE NATIONAL ECONOMIC RECOVERY EFFORT DURING THE COVID-19 PANDEMIC - Eva Haryatie,; Yudi Sutrasna,; Djamarel Hermanto, (International Journal of Social Science, 2023)
Global inflation due to rising food and energy prices and supply-demand imbalances. This has become the world's concern, especially Indonesia, in formulating policy strategies when the conditions before and after the Covid-19 pandemic affected the national economy and threatened non-military defense. The problems studied aim to determine National Economic Conditions Before & After the Covid-19 Pandemic and the Strategy of the Coordinating Ministry for Economic Affairs of the Republic of Indonesia in efforts to Restore the National Economy. This research uses a qualitative descriptive method with miles and huberman qualitative analysis techniques. The research results show that economic conditions at the time of the 2020 pandemic showed a significant decline due to the cessation of various economic activities as a result of the COVID19 pandemic. National Economic Conditions After the Covid-19 Pandemic that started in 2022, the global economy is showing recovery from the impact of the COVID-19 pandemic even though it was temporarily halted by the Omicron wave. This recovery is in line with the increasing implementation of global vaccinations, the increasing capacity of the health service system, and the opening up of economic activities in various countries. The results of the research and conclusions show that the National Economic Recovery Strategy is carried out through aspects (Ends), namely the long-term goal of the National Economic Recovery Strategy is to maintain price stability and increase food security to support people's purchasing power and national economic recovery, as well as increase Labor Absorption, In Aspects (Ways), namely the ways taken to achieve the long-term National Economic Recovery Strategy, namely Easing Community Mobility in line with Covid-19 control which leads to controlled Covid cases through the PPKM Policy and Setting travel requirements policies, Fiscal Policy as a Shock Absorber, etc. In Aspects (Means), namely the means used to achieve the long-term National Economic Recovery Strategy, namely: APBN as a Shock Absorber